Dinamika Psikologi Ibu yang Bekerja sebagai Guru dan Ibu Rumah Tangga dalam Mengasuh Anak - Lola Nabila (Indonesian Journal of Islamic Counseling, 2023)
ABSTRACT Maternal psychological dynamics is a force of energy that occurs in humans which influences their mental or psychological state to experience development and changes in daily behavior, both cognitive, emotional and behavioral. This research aims to determine the psychological dynamics of mothers who work as teachers and housewives in caring for children. The research subjects were 16 housewives who worked as teachers, from four sub-districts in Parepare City. The type of research is qualitative descriptive research, the data in this research was obtained from primary data and secondary data. The data collection techniques used were observation, interviews and documentation. The data analysis technique is using qualitative data analysis. The results of this research show a picture of the psychological dynamics of mothers who work as teachers and housewives in caring for children in Parepare City. Basically, psychological dynamics can be experienced by anyone because humans have three basic components, namely cognitive, emotional and behavioral components. The findings in the field show that the six teachers at different school levels prove that teachers have positive abilities and can respond to intelligence in managing psychological dynamics.